Female Education and Fertility in Nigeria - Nyarko, G.O. (University of Ghana, 2015)
Developing regions around the world now adopt policies and measures aiming at fertility decline. Results have shown rapid decline in Asia and Latin America and some parts of Africa. However, it has been slow in sub-Saharan Africa, especially Nigeria which has the largest population in Africa. Since fertility is the foundation for high population growth, it becomes imperative to look for factors that account for high fertility. Education of the female has been identified as the best contraceptive for fertility decline. This study examined effects of education and some intermediate variables on the level of fertility in Nigeria. The study used data from the 2013 Nigerian Demographic and Health Survey (NDHS). Data on 38,948 women extracted and analyzed using descriptive statistics for the univariate, ANOVA for the bivariate and multiregression. Two models were used in the regression analyses. In model one, all the control variables with the main independent variable were used against children ever born. The reason was to find the effect of those variables on fertility when intermediate variables were absent. Then in model two, the intermediate variables were combined with the control variables against children ever born. This was done to test the strength of association between the variables and children ever born with the presence of intermediary variables. The results of both models showed significant correlation between the variables and children ever born. The intermediate variables only looked at contraceptive use and age at first birth. The study confirmed that these variables can influence fertility in Nigeria. Contraceptive use is not widespread among the women. It was also evident that women with high status of wealth have lower number of children than the poorest. Religion, region of residence as well as ethnicity have an impact on fertility. The study concluded that those with lower levels of education have higher number of children than those with higher education.
Thesis (MA) - University of Ghana, 2015
Keywords: Female Education; Fertility; Contraceptive; Population Growth